4. PROPORTION AND SPECIES COMPOSITION OF DERMATOPHYTES CAUSING TINEA PEDIS BY MORPHOLOGY AND MOLECULAR BIOLOGY IN SMALL BUSINESS OWNERS IN NGHE AN PROVINCE (Vietnam Journal of Community Medicine, 2025)
Objectives: The study aimed to determine the proportion and species composition of dermatophytes causing tinea pedis among small business owners in Nghe An province.Methods: The experimental descriptive research method was employed with fungal culture in Saboraud Chromagar media with pH < 5.5 and antibiotics. The proportion and species composition was based on species identification keys, molecular biology and gene sequencing.Results: Among 126 fungal samples, the proportion of yeasts was 74.6%, followed by filamentous fungi accounting for 25.4%. Morphological identification, PCR-RFLP and sequencing detected 11 genera with 24 species. The most common pathogenic yeasts accounted for 74.7%, of which Candida albicans shared the highest rate of 61.7% (58/94). The pathogenic filamentous fungi accounted for 25.4% (32/126), of which the highest rate was Asfergilus flavus 46% (18/32). Some rare pathogenic species were also detected, including Talaromyces pinophilus, Curvularia lunata, Penicillium polonicum, Trigonopsis variabilis...Conclusions: 11 genera and 24 species of dermatophytes causing tinea pedis were identified.
Keywords: nấm; bàn chân